2016
DOI: 10.1158/1541-7786.mcr-15-0361
|View full text |Cite
|
Sign up to set email alerts
|

A DNA-binding Molecule Targeting the Adaptive Hypoxic Response in Multiple Myeloma Has Potent Antitumor Activity

Abstract: Multiple myeloma (MM) is incurable and invariably becomes resistant to chemotherapy. Although the mechanisms remain unclear, hypoxic conditions in the bone marrow have been implicated in contributing to MM progression, angiogenesis, and resistance to chemotherapy. These effects occur via adaptive cellular responses mediated by hypoxia-inducible transcription factors (HIFs), and targeting HIFs can have anti-cancer effects in both solid and hematological malignancies. Here, it was found that in most myeloma cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…We previously analyzed the expression patterns for HIF1α- and HIF2α-subunits in a panel of MM cell lines and found that HIF1α expression was mostly O 2 -dependent and expression levels were strongly induced by hypoxia, whilst HIF2α tended to be constitutively expressed (under both normoxic and hypoxic conditions) and this tended to be independent of O 2 levels [ 9 ] ( Fig 1A ). This implicated that differential regulation of the α-subunits is due to specific variations in the O 2 -sensing pathways so we assayed for expression of the two most common PHD isoforms, PHD2 and PHD3.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously analyzed the expression patterns for HIF1α- and HIF2α-subunits in a panel of MM cell lines and found that HIF1α expression was mostly O 2 -dependent and expression levels were strongly induced by hypoxia, whilst HIF2α tended to be constitutively expressed (under both normoxic and hypoxic conditions) and this tended to be independent of O 2 levels [ 9 ] ( Fig 1A ). This implicated that differential regulation of the α-subunits is due to specific variations in the O 2 -sensing pathways so we assayed for expression of the two most common PHD isoforms, PHD2 and PHD3.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Fig 1B , OPM2 cells were markedly more sensitive than 8226 to apoptosis (measured by cleavage of PARP and caspase 9) that was induced by culturing the cells under hypoxic conditions, perhaps because both HIF1α and HIF2α are constitutively expressed in 8226 cells. We tested this by using siRNA to target either HIF1α or HIF2α in 8226 cells (as described in [ 9 ]) and assayed the impact of silencing each subunit on the regulation of sensitivity to hypoxia. We have previously shown that siRNA silenced their targeted HIF gene by approximately 75–90% under both normoxic and hypoxic conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One such class of drugs that have been shown to target nucleotide moieties are polyamides. Several polyamides have been developed as inhibitors of gene expression and other biological effectors that bind double-stranded DNA in a sequence-specific manner (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18), and other polyamides have also been developed as broad-spectrum antivirals for papillomaviruses and polyomaviruses precisely because they do not show sequence-specific binding properties (19)(20)(21)(22)(23)(24)(25); J. K. Bashkin et al, unpublished data). Others have also since discovered nonspecific polyamide effects (26,27).…”
mentioning
confidence: 99%